Revisiting ecoenzymatic stoichiometry models for improved understanding of microbial resource limitations - Lifei Sun; Ji Chen; Yanci Qiao; Daryl L. Moorhead; Wolfgang Wanek; Raúl Ochoa-Hueso; Yongxin Lin (Soil Biology and Biochemistry, 2026)

SPVD-DETR: A novel real-time end-to-end object detector of sweetpotato virus disease from unmanned aerial vehicle ortho imagery - Fanguo Zeng; Ziyu Ding; Junzhi Chen; Yubin Lan; Lifei Huang; Yongxin Liu; Xuejun Yue; Lin Yuan (Computers and Electronics in Agriculture, 2026)

Identifying Geochemical Anomalies Associated with Vanadium Mineralization in Jiujiang City (China) Using Convolutional Neural Network with Attention Mechanism - Zenghua Li; Yong Jiang; Yuheng Lin; Yongpeng Ouyang; Lili Wang; Lifei Yang; Youguo Deng; Teng Deng; Deru Xu (Natural Resources Research, 2025)

“Three-birds, one-stone” biomimetic nanozyme system based on oxygen vacancy structure-regulated cascade reaction for inflammatory bowel disease - Tianliang Li; Zhaoming Wang; Zhijie Wang; Yihuan Pu; Lixing Lin; Zeyu Li; Lifei Chen; Xinting Liu; Bin Cao; Yingying Chen; Zhenzhen Li; Zixuan He; et al. (Chemical Engineering Journal, 2025)

Prospects of advanced oxidation processes for high-salinity coking wastewater treatment: A strategy to support sustainable management - Qili Peng; Jiangfang Yu; Ya Pang; Lifei Deng; Jing Tang; Jiajia Wang; Nile Wu; Lin Tang (Resources, Conservation and Recycling, 2025)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Exploring covariabilities of the high-summer subtropical upper-level pressure systems in the Northern Hemisphere - Ziyun Huang; Chundi Hu; Kaiqiang Deng; Zeming Wu; Chengyang Zhang; Tao Lian; Guoli Zhang; Lifei Lin; Song Yang (Atmospheric Research, 2024)

Extreme Mei-yu in 2020: Characteristics, causes, predictability and perspectives - Caihong Liu; Chundi Hu; Song Yang; Tao Lian; Chengyang Zhang; Lifei Lin; Fenying Cai (Earth-Science Reviews, 2023)

Acoustic telemetry system as a novel approach for evaluating the effective attraction of fish to artificial reefs - Shaoliang Lyu; Hagai Nsobi Lauden; Lifei Wang; Guobao Chen; Zhichao Wang; Kun Lin; Xuefeng Wang (Frontiers in Marine Science, 2023)
Due to there being a lack of suitable approaches for evaluating the effectiveness of artificial reefs, two experiments were designed to examine the feasibility of acoustic telemetry, a rapidly developing method for tracking aquatic animals. The first experiment was conducted to understand the deployment procedures of an acoustic telemetry system and determine the appropriate deployment of receivers’ spacing, while the second experiment was conducted to quantify the site fidelity and habitat use of 11 reef fish in the Fangchenggang artificial reef area in the northern South China Sea, China. The results indicated that the logistic regression model was an effective way to balance the detection probability at different distances between the range test transmitter and receiver, with above 50% detection probability within 240 m and 80% detection probability within 110 m. The residency index, as a quantification of site fidelity, was 0.85 ± 0.24. The 100% minimum convex polygon, 95% kernel utilization distribution, and 50% kernel utilization distribution, which are the indicators of habitat use, were 34,522.94 ± 35,548.95, 1,467.52 ± 1,619.05, and 236.01 ± 294.59 m 2 , respectively. High site fidelity and the small spatial scale of habitat use for reef fish demonstrated that artificial reefs were an effective man-made structure to attract fish. Overall, this study supports the feasibility of the acoustic telemetry system, indicating that it provides a good approach for quantifying the associations between artificial reefs and fish.

Generating phone-quality records to train machine learning models for smartphone-based earthquake early warning - Zengwei Zheng; Jiquan Wang; Lifei Shi; Sha Zhao; Jianmin Hou; Lin Sun; Lin Dong (Journal of Seismology, 2022)

Ammonium Removal by a Newly Isolated Heterotrophic Nitrification–Aerobic Denitrification Bacteria Pseudomonas Stutzeri SDU10 and Its Potential in Treatment of Piggery Wastewater - Lifei Chen; Jianqiang Lin; Deng Pan; Yilin Ren; Juan Zhang; Bo Zhou; Linxu Chen; Jianqun Lin (Current Microbiology, 2020)

Comprehensive transcriptomics and proteomics analyses of rice stripe virus-resistant transgenic rice - Yang Xu; Lvjie Bi; Zipeng Yu; Chao Lin; Liming Gan; Lifei Zhu; Haiyang Li; Yunzhi Song; Changxiang Zhu (Journal of Biosciences, 2019)

A female attractant for the blue gum chalcid, Leptocybe invasa (Hymenoptera: Eulophidae), from host plant (DH 201-2: Eucalyptus grandis × Eucalyptus tereticornis) - Tao Ma; Laijiao Lan; Na Lin; Lifei Zheng; Zhaohui Sun; Yizhen Li; Xiujun Wen (Arthropod-Plant Interactions, 2019)

Assessment of the baseline sensitivity and resistance risk of Colletotrichum acutatum to fludioxonil - Yangyang Gao; Lifei He; Wei Mu; Beixing Li; Jin Lin; Feng Liu (European Journal of Plant Pathology, 2018)

Activation of liver X receptor α protects amyloid β1–40 induced inflammatory and senescent responses in human retinal pigment epithelial cells - Bingling Dai; Chunyan Lei; Ru Lin; Lifei Tao; Yue Bin; Hui Peng; Bo Lei (Inflammation Research, 2017)